2023
DOI: 10.1021/acsami.2c19198
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nanoplatform for Mild Microwave-Enhanced Thermal, Antioxidative, and Chemotherapeutic Treatment of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is usually associated with excessive proliferation of M1-type proinflammatory macrophages, resulting in severe hypoxia and excess reactive oxygen species (ROS) in the joint cavity. Inhibiting M1-type proinflammatory macrophages and/or repolarizing them into M2 phenotype anti-inflammatory cells by alleviating hypoxia and scavenging ROS could be a promising strategy for RA treatment. In this work, a microwave-sensitive metal–organic framework of UiO-66-NH2 is constructed for coating a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Synthesis of UiO-66-NH 2 and UiO-66-NH 2 @HA (UH): UiO-66-NH 2 was synthesized according to a previous method performed by the authors. [42] Specifically, anhydrous ZrCl 4 (42 mg, 0.18 mm) and NH 2 -BDC (33 mg, 0.18 mm) were dissolved in 3.5 mL DMF, and 0.1 mL deionized water was added. Then, 1.7 mL glacial acetic acid was added to the solution and the mixture was sonicated for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Synthesis of UiO-66-NH 2 and UiO-66-NH 2 @HA (UH): UiO-66-NH 2 was synthesized according to a previous method performed by the authors. [42] Specifically, anhydrous ZrCl 4 (42 mg, 0.18 mm) and NH 2 -BDC (33 mg, 0.18 mm) were dissolved in 3.5 mL DMF, and 0.1 mL deionized water was added. Then, 1.7 mL glacial acetic acid was added to the solution and the mixture was sonicated for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…[48][49][50] It has been reported by us and others that UiO-66-NH 2 with a porous structure is one of the excellent microwave sensitizers, and 0.9% NaCl (saline) in UiO-66-NH 2 enhances the sensitivity of microwaves. [42,51] As shown in Figure S8, Supporting Information, UiO-66-NH 2 with different concentrations (5, 10, and 15 mg mL −1 ), water, and saline were exposed to microwave irradiation (3 W, 450 MHz) for 5 min. The results showed that the temperature of 15 mg mL −1 UiO-66-NH 2 increased to 48.3 °C, while that of water and saline only reached 29.9 and 37.3 °C.…”
Section: Evaluation Of the Microwave Heating Properties Of Umnementioning
confidence: 99%
See 2 more Smart Citations
“…In the context of biomedical applications, CeO 2 NPs have been studied for their redox enzyme mimetic efficiency and biocompatibility. 15–20 The redox properties of CeO 2 NPs are based on the reversible transition between Ce 4+ (defectless) and Ce 3+ (oxygen vacancy) states within its cubic fluorite structure ( Fm 3̄ m ), both states having significant populations in CeO 2 NPs due to their propensity for oxygen vacancies. The antioxidant properties of CeO 2 NPs in the presence of ROS ( • O − 2 , H 2 O 2 ) occurs through the oxidation of surface Ce 3+ states, as described by the following equations:Ce 3+ + • O 2 − + 2H + → Ce 4+ + H 2 O 2 2Ce 3+ + H 2 O 2 + 2H + → 2Ce 4+ + 2H 2 O…”
Section: Introductionmentioning
confidence: 99%